Process Management - Pomffyova, Maria (IntechOpen, 2010)
The content of the book has been structured into four technical research sections with total of 18 chapters written by well recognized researchers worldwide. These sections are: 1. process and performance management and their measurement methods, 2. management of manufacturing processes with the aim to be quickly adaptable after real situation demands and their control, 3. quality management information and communication systems, their integration and risk management, 4. management processes of healthcare and water, construction and demolition waste problems and integration of environmental processes into management decisions.